Acordo de Escazú: Normatividade em Paralelo com a Legislação Ambiental Brasileira - Mariel Cavalin dos Santos (2024)
SANTOS, Mariel Cavalin dos. Escazú Agreement: Normativity in Parallel with Brazilian Environmental Legislation. Dissertation (Master's in Law) - Universidade Federal do Mato Grosso do Sul, Campo Grande, 2024. Advisor: Prof. Dr. Lívia Gaigher Bósio Campello. The aim of this study is to analyze whether there is compatibility between Brazilian environmental legislation and the country's domestic system for protecting the environment, when compared to the pillars of the Regional Agreement on Access to Information, Public Participation and Access to Justice in Environmental Matters in Latin America and the Caribbean, also known as the Escazú Agreement. The agreement was drawn up with a view to promoting environmental democracy and the innovative international proposal for protecting environmental defenders. The idea that natural resources were inexhaustible, paired with climate change resulting from human actions, which became a factor of high environmental impact during the contemporary Anthropocene event, resulted in a global scenario of urgency to change human behavior regarding natural resources, especially in terms of guaranteeing their survival. International treaties are one of the ways of establishing global environmental governance and the search for sustainable development strategies. The guarantee of feeding the human population and preserving the environment for present and future generations is possible if there is a balance between the two axes. This is a research proposal using the deductive method and a qualitative approach, of the exploratory and descriptive type, with the use of bibliographical review procedures on the relevant topics and a documentary examination of international instruments and national legal provisions on the environment. The purpose of this is to subsidize the comparative study outlined. The research concluded that Brazil has sufficient domestic environmental legislation that is compatible with the pillars of the Escazú Agreement and promotes environmental democracy in the legislative sphere. The contribution of this work is to analyze whether Brazil should join the Escazú Agreement, since it has been signed but not yet ratified. Keywords: Escazú Agreement; Environmental Democracy; Anthropocene; Environmental Governance; Sustainable Development.